Evaluation of antifungal activity of neolamarckia cadamba leaf extract - Nuraini, binti Azman (Universiti Malaysia Sarawak (UNIMAS), 2016)
This project focused on antifungal activity of Neolamarckia cadamba leaf extract in order to evaluate the effect of aqueous and ethanol extracts from white kelampayan leaf against the most important phytopathogenic fungi, Aspergillus flavus, Aspergillus niger and Fursarium solani by poisoned food technique. Different concentrations (5, 15, 25, 50 and 100 mg/ml) prepared form these extracts was inhibited the growth of the experimental fungi and the effect inconsistent with concentration. In thesolvent extracts tested, aqueous and ethanolleaf extract gave the highest perentage of inhibition against Aspergillus niger followed by Fusarium solani and Aspergillus flavus. However, aqueous leaf extract have higher percentage of growh inhibition with 31-45% compared to ethanol leaf extract for all experimental fungi which ot ws slightlu not effective in antifungal activity of N. cadamba.